Molecular Imaging for Lung Cancer: Exploring Small Molecules, Peptides, and Beyond in Radiolabeled Diagnostics - Meliha Ekinci; Tais Monteiro Magne; Luciana Magalhães Rebelo Alencar; Pierre Basilio Almeida Fechine; Ralph Santos-Oliveira; Derya Ilem-Özdemir (MDPI AG, 2024)
It is evident that radiolabeled drug delivery systems hold great promise in the field of lung cancer management. The combination of therapeutic agents with radiotracers not only allows for precise localization within lung tumors but also enables real-time monitoring of drug distribution. This approach has the potential to enhance targeted therapy and improve patient outcomes. The integration of advanced imaging modalities, such as positron emission tomography (PET) and single-photon emission computed tomography (SPECT), has played a crucial role in the non-invasive tracking of radiolabeled drugs. These techniques provide valuable insights into drug pharmacokinetics, biodistribution, and tumor-targeting efficiency, offering clinicians the ability to personalize treatment regimens. The comprehensive analysis of preclinical and clinical studies presented in this review underscores the progress made in the field. The evidence suggests that radiolabeled drug delivery systems have the potential to revolutionize oncology by offering precise, targeted, and image-guided therapeutic interventions for lung cancer. This innovative approach not only enhances the effectiveness of treatment but also contributes to the development of personalized medicine strategies, tailoring interventions to the specific characteristics of each patient's cancer. The ongoing research in this area holds promise for further advancements in lung cancer management, potentially leading to improved outcomes and quality of life for patients.